Sterowanie rozwojem gospodarczym regionu - Trojanek, Maria (Wydział Prawa i Administracji UAM, 1992)
The article presents the problems connected with the shaping of the development of a region in new socio-economic and political conditions. The author points to the circumstances in which regional authorities may construct the program of such development, and presents the instruments to be used for ensuring a harmonious development of a given region. Besides, the author presents some methodological conceptions to be utilized in the process of coordinating developmental aims of entities cariying out the economic activity in a given region.
Regional economic development controls